Japa Mantra and Offerings in the Walagara Wedding Tradition of the Tengger Tribe in Ngadas Village, Poncokusumo: A Study of Islamic Law - Hakam Efendy; Syamsu Madyan; Nur Hasan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The Walagara tradition in Tenggerese weddings in Ngadas Village, Malang Regency, is a form of local wisdom that serves as a customary legalization of marriage. This tradition involves two main elements: the recitation of mantras and the presentation of offerings, understood as a medium of spiritual communication with the gods, water maidens, and ancestral spirits to request safety and blessings for the bride and groom. This study aims to analyze the symbolic meaning of the Walagara tradition and its legal implications from an Islamic legal perspective through an 'urf' approach. The method used is qualitative-descriptive with Clifford Geertz's symbolic-interpretive analysis. The results indicate that the mantras serve as a spiritual medium, recited by traditional shamans in the ancient Tenggerese language, accompanied by offerings containing cosmological meaning. Although the Tenggerese Muslim community continues to participate in this tradition, interpreting it as a form of cultural respect, under Islamic law, this practice is categorized as 'urf fāsid' due to its potential to contain elements of polytheism. Therefore, a wise approach to da'wah is needed to ensure that cultural preservation remains in line with the principles of monotheism.